Podium - The further and higher education unit for the 2012 games (2010)
Podium is the Further and Higher Education Unit for the 2012 Games and was established in 2007 as a division of London Higher, which is the umbrella body representing more than 40 universities and colleges in London. Podium functions as a platform on which to build the nationwide engagement of FE and HE with London 2012. The unit is funded by the Higher Education Funding Council for England as well as the Skills Funding Agency and is directed by a Board of leading figures from the sectors. Working with key stakeholders and alongside the Games authorities, Podium`s role is to communicate Games related opportunities, support the development of programmes and share examples of good practice across the sectors. Simply put, Podium`s core functions are to communicate, collaborate and enhance. Although an independent body, Podium works extremely closely with the London Organising Committee of the Olympic and Paralympic Games (LOCOG) with the Head of the unit being seconded into LOCOG on a part-time basis. The FE and HE sectors have played an integral role for Team GB at previous Olympic and Paralympic Games. For example; more than 50 per cent of our Beijing 2008 medallists were students or graduates. The sectors` involvement with London 2012 is much greater and wider though, as this report, The Engagement of Further and Higher Education with the London 2012 Olympic and Paralympic Games, commissioned by Podium from the Centre for Sport, Physical Education & Activity Research (SPEAR) at Canterbury Christ Church University demonstrates.Podium's strategic direction is shaped by a Board and Chaired by Professor Geoff Petts, Vice-Chancellor of the University of Westminster. The Board is made up of representatives from both Further and Higher Education and a range of strategic stakeholders. Podium continues to be hosted by London Higher and is based alongside their offices in Senate House. The unit is funded by the Higher Education Funding Council for England (HEFCE) and the Learning and Skills Council (LSC) with additional funding from the Higher Education Funding Council of Wales (HEFCW).